TNFAIP9 protects against the development of the early stage of chronic kidney disease: Focus on inflammation and fibrosis - Ying Chen; Yanqiu Li; Deyu Zhang (PLoS ONE, 2025)
Tumor necrosis factor alpha-induced protein 9 (TNFAIP9) is a crucial effector molecule that protects cells from inflammatory and metabolic damage. This study focuses on investigating the role and regulatory mechanisms of TNFAIP9 in the progression of chronic kidney disease (CKD). By analyzing CKD-related datasets from the GEO database, we discovered that TNFAIP9 was upregulated in CKD patients and CKD mice compared to their normal controls. To elucidate the functional role of TNFAIP9, we established a mouse model of CKD through a two-step 5/6 nephrectomy (Nx). The experimental mice were transduced with an adenoviral vector to express TNFAIP9. The results showed that mice undergoing 5/6-Nx developed evident renal impairment, inflammation, and fibrosis. Overexpression of TNFAIP9 resulted in the remission of renal impairment, a decreased inflammatory response, and a reduced expression of fibrotic markers. In vitro, human renal tubular epithelial human kidney-2 (HK-2) cells were exposed to tumor necrosis factor-alpha (TNF-α) or transforming growth factor-beta (TGF-β) to simulate inflammatory and fibrotic conditions, respectively. Then, the overexpression plasmid or small interfering RNA (siRNA) targeting TNFAIP9 was transfected into HK-2 cells to either overexpress or knock down the target protein. Overexpression of TNFAIP9 reduced the TNF-α-induced inflammatory response, while its knockdown amplified it. Likewise, overexpression of TNFAIP9 decreased the TGF-β-induced fibrosis, whereas its knockdown heightened it. In summary, it is suggested that TNFAIP9 plays a protective role against the early stage of CKD by suppressing renal inflammation and fibrosis. Therefore, targeting TNFAIP9 could be a promising therapeutic approach for CKD.